Relevansi Hadis Dalam Mengatasi Problem Santri Di Pesantren Cipansor Kab. Tasikmalaya(Studi Kasus pada Aspek Pendidikan, Sosial, dan Pengembangan Karakter) - Helmi, Cecep; Muhammad Zuldin; Aep Kusnawan; Yusuf Zainal Abidin (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the relevance of hadith in addressing the problems faced by students at the Cipansor Islamic Boarding School in Tasikmalaya Regency, focusing on three main aspects: education, social, and character development. The background of this study is based on the gap between the idealism of pesantren education and the reality faced by santri, such as low motivation to learn, difficulties in social adaptation, and weak internalization of Islamic character values. The hadith of the Prophet Muhammad SAW is seen as a source of Islamic teachings that has the potential to provide solutions and be applied in overcoming these problems. This research uses a qualitative approach with a case study method and data collection techniques through in-depth interviews, participatory observation, focus group discussions, and document analysis. The results of this study are expected to identify the typology of santri problems, analyze the concepts and methodology of relevant hadith application, evaluate the implementation models used by ustadz and kyai, and formulate an ideal model for hadith implementation in santri guidance. This research not only contributes theoretically to the study of applied hadith in Islamic education but also offers practical solutions for the development of a contextual pesantren education system rooted in authentic Islamic sources.